2018
DOI: 10.1532/hsf.2177
|View full text |Cite
|
Sign up to set email alerts
|

Use of the ClearSight® System for Continuous Noninvasive Hemodynamic Monitoring during Heart Valve Interventions: Review of the Literature and Single-Site Experience

Abstract: During interventional and structural cardiology procedures, such as mitral valve (MitraClip, BMV), aortic valve (TAVR, BAV), tricuspid valve (MitraClip), left atrial appendage (Watchman, Lariat), atrial septum (ASD/PFO closure), and coronary artery intervention (high-risk PCI), among others, patients are at a high risk of hemodynamic instability and require continuous monitoring. This is conventionally achieved through arterial catheterization and transpulmonary thermodilution. However, such invasive technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…Gellert and Bramlage suggested heart valve interventions/surgery as a possible application for the ClearSight™ system for (REF). In this review, the bias of MAP in 16 studies from 2009 to 2018 was from -4,2 (SD 13,7) mmHg to 6,2 (SD 11,7) mmHg.,[ 16 ] which is comparable to the difference found in our study. They conclude that the ClearSight™ system can be used to accurately monitor hemodynamics during these interventions.…”
Section: Discussionsupporting
confidence: 92%
“…Gellert and Bramlage suggested heart valve interventions/surgery as a possible application for the ClearSight™ system for (REF). In this review, the bias of MAP in 16 studies from 2009 to 2018 was from -4,2 (SD 13,7) mmHg to 6,2 (SD 11,7) mmHg.,[ 16 ] which is comparable to the difference found in our study. They conclude that the ClearSight™ system can be used to accurately monitor hemodynamics during these interventions.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the non-invasive blood pressure measurement during fast heart stimulation, accurately and immediately showed significant alternations in the haemodynamic parameters [ 55 ]. Similar results in accuracy of blood pressure and cardiac output were obtained in two studies in which the ClearSight system was applied and compared to the invasive monitoring in patients with aortic and mitral valve replacement [ 56 , 57 ]. Another study found that an agreement between NICO and invasive hemodynamic monitoring was clinically acceptable, but had a tendency to underestimate CO compared to the termodilution method [ 49 ].…”
Section: Non-invasive Haemodynamic Monitoring and Cardiosurgery And Interventional Cardiologysupporting
confidence: 65%
“…However, Eley and coworkers argued that NIBP cuffs were not based on the mid-arm circumference, as recommended by the American Heart Association [ 36 ] and that patient allocation to correctly sized cuffs is essential for a validation [ 27 ]. Our study did not focus on a cost-effectiveness analysis for the different blood pressure monitoring methods used in the bariatric population and non-manufacturer derived data on this subject is yet limited [ 37 , 38 ]. The acquisition costs could be a barrier to the introduction in anesthesia departments [ 39 ].…”
Section: Discussionmentioning
confidence: 99%